“The Whole ME presented itself. KABOOM!”: Expressive Arts and Critical Reflection - Gardner, Morgan (Alberta Journal of Educational Research, 2012)
The importance of critical reflection in higher education highlights the importance of creating rich learning opportunities for students. Expressive arts (e.g., poetry, drama) ignites such opportunity drawing from more than students’ logical-cognitive understandings to include students’ creative, multi-modal and experiential capacities. This paper provides one university instructor’s reflective account of how an expressive arts final assignment (in a non-arts course) invited students to use the languages of the arts to enhance their critical reflection of course learning. Students’ expanded agency and complexity of understanding illustrated expressive arts as a valuable facet of academic work. L’importance de la réflexion critique en éducation postsecondaire rehausse l’intérêt de créer des occasions riches en apprentissage pour les étudiants. Les arts expressives (p. ex. la poésie, les arts de la scène) offrent de telles occasions en allant chercher au-delà des connaissances logiques et cognitives des étudiants pour puiser dans leurs capacités créatrices, multimodales et expérientielles. Cet article présente le compte rendu d’un professeur à l’université sur le rôle d’un travail final reposant sur les arts expressives (dans un cours ne relevant pas du domaine des arts) qui a encouragé les étudiants à utiliser le langage des arts pour mettre en valeur leur réflexion critique du cours. La marge de manœuvre élargie des étudiants et la complexité accrue de leurs connaissances reflètent le rôle important des arts expressives dans le travail académique.